Retrospective Analysis of Surgical Treatment Results of Postinfarction Ventricular Septal Rupture - R. A. Aliyev (Ukrainian Journal of Cardiovascular Surgery, 2021)
Ventricular septal rupture (VSR) is the most dramatic complication of acute myocardial infarction (MI). It manifests itself most often in the first week after infarction, with the maximum fatal complications occurring on day 1 and day 3–5 after MI. Patients receiving conservative treatment mostly die of progressive heart failure within few hours or days. Even now, in the era of endovascular interventions, surgical treatment remains the gold standard for the treatment of this pa-thology. Our research is mainly aimed at studying the factors of operative mortality, describing our methods of treatment and analyzing the survival rate and long-term outcomes after surgical treatment of this pathology.We studied 90 patients with postinfarction VSR who underwent surgical intervention in 2002–2019. Twelve of them were operated at the Central Clinical Hospital in Baku, and 78 at the National Amosov Institute of Cardiovascular Surgery in Ukraine. The mean age of the patients was 59.9 ± 9.59 years, 65 (72.2%) were men and 25 (27.8 %) were women. Fifteen (16.6%) patients were smokers, 31 (34.4%) were diabetic, 70 (77.7%) patients had arterial hypertension, 62% of patients had NYHA class III heart failure with average ejection fraction of 43.9 ± 10.4%. According to the results of coronary angiography, single vessel stenosis of the coronary arteries was detected in 18 (20%), two-vessel lesion in 32 (35.5%), and three-vessel lesion in 40 (44.4%) patients. There were no patients with left main coronary artery (LMCA) stenosis.Long-term results of surgical treatment were followed for 1 to 8 years, on average in 18 (28.6%) patients. Within 1, 3 and 8 years 17, 12 and 2 patients were examined, respectively. Good results within 5 and 10 years after surgical treatment were observed in 87.5% and 64.3% patients, respectively.Repeated complaints in our group and those observed in the literature are associated with worsening of heart failure after venticulotomy and changes in the geometry of the left ventricle.Recurrence of heart failure and coronary symptoms within 3 years and after 3 to 8 years were observed in 6 (33.3%) and 3 (25%) patients, respectively. Repeated endovascular revascularization was performed in 5 patients. ICD was im-planted in 4 patients, and in 2 patients CRT-D was implanted within 4 years 2 months and 7 years, respectively.There were no hemorrhagic complications within 8 years. Four (22.2%) patients died in the long-term period, the cause of death was unknown.In intensive care department the treatment strategy suggested hemodynamic stabilization with the help of conserva-tive therapy and IABP.The patients who underwent surgery in ≥ 3 weeks after the diagnosis of postinfarction VSR survived within 30 days after surgery. Delayed planned recovery is stipulated by the formation of scar tissue in the myocardium, which enables to facilitate the technical aspects of recovery. The time of the operation depends mainly on hemodynamic status of the patient. Patients with cardiogenic shock should undergo immediate surgical treatment.